The Intensive Arab Language Course for Indonesian School Students in The Form of "Arab Camp" Program - Suryadarma, Yoke (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2017)
Arab language camp was intensive course of Arabic language that was implemented by students of Arabic Language Department at University of Darussalam Gontor and supervised by lecturers in Arabic Language Department. The implementation of this program was limited in one point to develop speech skill among learners. This research used qualitative descriptive approach. The data in this research was taken by researcher from observation, interview and written documents. This approach involves integrated linguistic activities in the classroom or out side of classroom to help learners in raising and developing their language in the four language skills generally, and speech skill spesificly.